Microwave-Enhanced Crystalline Properties of Zinc Ferrite Nanoparticles - Ochmann, Martin; Vrba, Vlastimil; Kopp, Josef; Ingr, Tomáš; Malina, Ondřej; Machala, Libor (Nanomaterials (Basel, Switzerland), 2022)
Two series of ZnFe2O4 mixed cubic spinel nanoparticles were prepared by a coprecipitation method, where a solution of Fe3+ and Zn2+ was alkalised by a solution of NaOH. While the first series was prepared by a careful mixing of the two solutions, the microwave radiation was used to enhance the reaction in the other series of samples. The effect of the microwave heating on the properties of the prepared particles is investigated. X-ray powder diffraction (XRD), 57Fe Mössbauer spectroscopy and magnetometry were employed to prove the cubic structure and superparamagnetic behavior of the samples. The particle size in the range of nanometers was investigated by a transmission electron microscopy (TEM), and the N2 adsorption measurements were used to determine the BET area of the samples. The stoichiometry and the chemical purity were proven by energy dispersive spectroscopy (EDS). Additionally, the inversion factor was determined using the low temperature Mössbauer spectra in the external magnetic field. The microwave heating had a significant effect on the mean coherent length. On the other hand, it had a lesser influence on the size and BET surface area of the prepared nanoparticles.
Keywords: microwave synthesis; coprecipitation method; inversion factor; zinc ferrite; crystal growth